La reacción penal del Estado frente al terrorismo transnacional = Criminal law and the State’s reaction to international terrorism - Mizrahi, Esteban (Veritas, 2013)
The main assumption of this paper is that the contemporary transformation of the State and its role in the Western world has generated a significant reaction in the area of criminal law and this has led to a substantial reformulation of theories of punishment to explain the emergence of new crimes and criminal types. The paper is articulated as follows: First, I analyze the relationship between public security, the State and penalty in the modern World to show how the contemporary crisis of State sovereignty expresses the need for a new theoretical framework to explain the relationship between these terms (I). Second, I introduce the model developed by Niklas Luhmann to clarify the role of law in complex societies and the specific criminal developments from a functionalist approach proposed by Günther Jakobs (II). Third, I discuss the treatment of transnational terrorism as a phenomenon that allows to evaluate both the limits and the presuppositions of criminal law in democratic states (III). I conclude by offering some tentative answers to the question of the limits and the presuppositions of the State’s reaction in the case of criminal law (IV)